Mariano Moreno, la Historia de las dos Indias y el Plan de Operaciones - Agustín Mackinlay (Les Cahiers ALHIM)
The digitization of abbé Raynal’s Histoire des deux Indes (HDI) opens the way to a new interpretation of the writings of Mariano Moreno, the leader of Buenos Aires’s revolutionary Junta in 1810. The article provides the first systematic account of Raynal’s (and Diderot’s) influence on the political thought of Moreno. We document the decisive impact of HDI on his ideas and on his policies. Traces of Raynal’s book are also prominently on display in the Plan of Operations, a document widely attributed to Moreno, in which a number of violent measures are recommended. While some see the Plan of Operations as a propaganda pamphlet written in Montevideo in 1813 in order to discredit the Buenos Aires Junta, we show that it is largely compatible with Moreno’s political views. Deeply influenced by the image of the revolutionary leader in HDI, Moreno establishes an implicit distinction between the founding moment (usually marred by violence) and the subsequent need for a peaceful administration based on balanced government. Seen in this light, the Plan of Operations is clearly compatible with Moreno’s writings in Gazeta de Buenos-Ayres.